Antibacterial activity of TiO2 and TiO2 composites nanopowders prepared by hydrothermal method. (31st May 2019) - Rasheed, Rashed Taleb; Mansoor, Hadeel Salah; Qasim, Bashar Hussein
Abstract: In this work, some inorganic metal oxides such as titanium dioxide (TiO2 ), iron oxide (Fe2 O3 ) and indium oxide (In2 O3 ) nanopowders were prepared by a hydrothermal technique. The TiO2 was mixed separately with Fe2 O3, In2 O3 and both mixtures were used to prepare three composite nanopowders (TiO2 –Fe2 O3, TiO2 –In2 O3, and TiO2 –Fe2 O3 –In2 O3 ) at (1:1, 1:1 and 1:1:1) mole ratio respectively. The best conditions at 400 °C annealing temperatures were determined. The nanopowders were investigated and analyzed at different parameters; structure and surface morphology of powders were characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM) techniques, atomic force microscopy (AFM), and fourier transform infrared spectroscopy (FTIR). The results of antibacterial activity for TiO2 and its composites with two types of bacteria Gram-negative ( Escherichia coli ) and Gram-positive ( Staphylococcus Aureus ), showed an increase in activity with increasing concentration of TiO2 and annealing temperature. It was observed that the prepared composites were more effective in inhibiting different bacterial growth.